Klebsiella pneumoniae in Singapore: Hypervirulent Infections and the Carbapenemase Threat - Chew, Ka Lip; Lin, Raymond T. P.; Teo, Jeanette W. P. (Frontiers in Cellular and Infection Microbiology, 2017)
Klebsiella pneumoniae remains a major pathogen responsible for localized infections such as cystitis and pneumonia, and disseminated infections that may result in severe sepsis and death. Invasive disease such as liver abscesses and endogenous endophthalmitis are associated with capsular serotypes K1 and K2. These infections require a prolonged course of antimicrobial treatment which has evolved over the years from inpatient treatment to outpatient parenteral antibiotic therapy. The emergence of plasmid-mediated resistance began with extended-spectrum β-lactamases (ESBLs) and AmpC β-lactamases. This was followed by carbapenemase genes and now plasmid transmissible colistin resistance (mcr), thus limiting viable treatment options. Plasmid-mediated carbapenemase production in Singapore was first reported in 1996. Carbapenemase production has since become the predominant mechanism of carbapenem resistance and incidence rates continue to increase over time. Although carbapenemases can occur in all Enterobacteriaceae, K. pneumoniae are the most common carrier of carbapenemase genes. Alternative treatment options are urgently required before the simplest infections, let alone invasive infections are left potentially untreatable. Clinical management requires guidance from robust laboratory testing methods to optimize patient outcomes. We explore past and present trends in treatment of K. pneumoniae infections, and discuss future treatment options and gaps in knowledge for further study.